Hubungan Pengetahuan dengan Penggunaan Mobile JKN : Studi Kasus RS Santa Elisabeth Medan - Simbolon, Pomarida; Saragih, Pestaria; Harefa, Jatmika Nonifili (Lontara Journal of Health Science and Technology, 2024)
Mobile JKN is a form of digital transformation in the form of an application that can be used by JKN participants anywhere and at any time and is expected to reduce queues when registering patients. At the Santa Elisabeth Hospital in Medan, there are still patients who do not understand how to use the JKN mobile application because the level of knowledge about Mobile JKN is still relatively low, especially in patients who have low education and are entering old age so that the available health services are not utilized optimally. The aim of this research is to identify the relationship between knowledge and the use of mobile JKN at Santa Elisabeth Hospital Medan in 2024. The analytical research design uses a cross sectional approach. The sample for this research was 95 respondents with the sampling technique being accidental sampling. The instrument used was a questionnaire. Data analysis using the Chi-square test. The results of this study showed that 80 patients' knowledge was in the good category (84.2%), 51 people's use of mobile JKN was in the good category (53.7%). The results of the Chi-square test obtained a p-value of 0.002 (p<0.05) indicating that there is a significant relationship between knowledge and the use of mobile JKN at Santa Elisabeth Hospital Medan in 2024.